Upaya Program Studi Ilmu Perpustakaan dan Informasi Islam IAIN Curup dalam mewujudkan pustakawan profesional dan kompetitif menghadapi era 5.0 - Rodin, Rhoni; Rizkyantha, Okky; Perdana, Moga (Al-Kuttab : Jurnal Kajian Perpustakaan, Informasi dan Kearsipan, 2024)
The purpose of this study is to analyze the efforts of the Islamic Library and Information Science Program (Prodi IPII) at IAIN Curup in creating professional and competitive librarians for the era of 5.0. This research is descriptive and qualitative. Data was collected through observation, interviews, and documentation. The findings show that Prodi IPII has several strengths, such as an adaptive curriculum in line with current advancements, competent and dedicated lecturers, and various student competence development programs. However, there are also weaknesses that need to be addressed, such as integrating Islamic values into the curriculum and ensuring all lecturers are proficient in information technology. Opportunities for the program include the need for librarians in Rejang Lebong Regency and support from national standards for school/madrasah libraries. The main challenges are adapting to technological developments and meeting the public's information needs in the digital era. To achieve professional and competitive librarians in the era of 5.0, the Islamic Library and Information Science Program at IAIN Curup implements several strategies: 1) Curriculum Development, 2) Improving Competence of Lecturers and Students, 3) Instilling Character Values, 4) Enhancing the Quality of Learning, 5) Developing Cooperation Networks, 6) Increasing Scientific Publications, and 7) Improving Facilities and Infrastructure